MANAJEMEN INOVASI PEMBELAJARAN BERBASIS DIGITAL DALAM PENINGKATAN MUTU PENDIDIKAN DI MA SAQA - Umi Kulsum; Irzak Yuliardy Nugroho; Sollah Solehudin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the management of digital-based learning innovations in an effort to improve the quality of education at MA SAQA. The study used a qualitative approach with a descriptive design; Data collection was conducted through observation, interviews, and document review involving the principal, teachers, and students. The findings show that the management of digital innovation in madrasas takes place through a series of activities: planning, implementation, and evaluation. In the planning stage, the school establishes a strategy for integrating technology into the curriculum and establishes supporting policies. During implementation, teachers utilize various digital media such as interactive presentations, learning videos, and bold communication platforms to enrich the teaching and learning process. The evaluation stage is carried out to assess the effectiveness of technology utilization and identify emerging obstacles so that improvements can be designed. Several factors that support successful implementation include the institution's commitment to the use of technology, the readiness of teachers to adopt new methods, and the enthusiasm of students to use digital devices. Conversely, obstacles that often arise include limited facilities and infrastructure (e.g., the number of devices and facilities is not evenly distributed) and unstable internet connectivity. The positive impact of digital-based learning innovations is reflected in the increased effectiveness of the learning process, increased student motivation and participation, and the development of digital teacher competencies. Furthermore, learning becomes more flexible because students can access a wider range of learning resources independently. Based on these results, several steps are recommended to optimize the implementation of digital learning at MA SAQA: strengthening policies that support digital transformation, improving the quality and equity of technology infrastructure and connectivity, and providing ongoing training and mentoring for educators. The implementation of these steps is expected to strengthen the effectiveness of digital learning innovations and contribute to improving the quality of education in madrasas.